Implementing an Educational Module for Orthopaedic Residents Placing Skeletal Traction. (14th April 2023) - Nielsen, Ena; Walterscheid, Zakkary; Beingessner, Daphne; Kleweno, Conor
Abstract : Introduction: Although placement of a distal femoral traction (DFT) pin is a relatively simple procedure used to stabilize femoral and pelvic fractures, it places patients at risk of iatrogenic vascular, muscular, or bony injury. We designed and implemented an educational module combining theory and practical experience to standardize and improve resident teaching on the placement of DFT pins. Methods: We introduced a DFT pin teaching module into our second-year resident "boot camp, " which is used to help prepare residents for taking primary call in the emergency department at our level I trauma center. Nine residents participated. The teaching module included a written pretest, an oral lecture, a video demonstration of the procedure, and a practice simulation on 3D printed models. After completing the teaching, each resident underwent a written examination and proctored live simulation involving 3D models using the same equipment available in our emergency department. Pre-teaching and post-teaching surveys were used to assess resident experience and confidence with placing traction in the emergency department. Results: Before the teaching session, the rising postgraduate year 2 residents scored an average of 62.2% (range, 50% to 77.8%) on the DFT pin knowledge quiz. This improved to an average of 86.6% (range, 68.1% to 100%) ( P = 0.0001) after the teaching session. After completing the educational module, they also demonstrated an improvement in confidence with the procedure, from 6.7 (range, 5 to 9) to 8.8 (range, 8 to 10) ( P = 0.04). Discussion: Despite reporting high levels of confidence in their ability to place traction pins before starting the postgraduate year 2 consult year, many residents also reported anxiety around the accurate placement of traction pins. Early results of our training program showed improved resident knowledge of safe placement of traction pins and improved confidence with the procedure.